Synthesis, structural characterisation, and synthetic application of stable seleniranium ions. Issue 12 (6th March 2019) - Bock, Jonathan; Daniliuc, Constantin G.; Bergander, Klaus; Mück-Lichtenfeld, Christian; Hennecke, Ulrich
Abstract : Stable seleniranium ions were prepared, their solid state structures determined and their application as highly efficient selenenylating agents was demonstrated. Abstract : Stable seleniranium ions were prepared from easily available stable bromiranium ions and diselenides. The solid state structure of the obtained seleniranium ions was determined by X-ray crystallographic analysis and their alkene-to-alkene transfer was investigated by NMR techniques. The rapid alkene-to-alkene transfer of the selenium group enabled the application of the seleniranium ion salts as selenenylating agents, which led to very efficient and highly diastereoselective, selenium-induced polyene-type cyclisations of terpene analogues.